EFEKTIFITAS TERAPI DZIKIR TERHADAP TINGKAT KECEMASAN IBU HAMIL DI LEMBAGA PEMASYARAKATAN (LP) WANITA KELAS II A SUKUN MALANG - Mohammad Tulus; Nely Ilmi Qoth'iyah (El-QUDWAH, 2013)
EFEKTIFITAS TERAPI DZIKIR TERHADAP TINGKAT KECEMASAN IBU HAMIL DI LEMBAGA PEMASYARAKATAN (LP) WANITA KELAS II A SUKUN MALANG Oleh:Mohamad Tulus Dosen FITK UIN Maulana Malik Ibrahim Malang Email: moh.tulus@gmail.com Nely Ilmi Qoth’iyah Dosen Sekolah Tinggi Keguruan Maskumambang Dukun Gresik Email: neli.ilmi@gmail.com Abstract This study aimed to know the effect of dhikr toward level of anxiety of pregnant women with quasi- experimental research design with pre - test - post-test control group design. Subjects were pregnant women in prison (LP) in Women Prison Malang that chosen with purposive random sampling and  divided in experimental group and control group. Data was collected through interviews, observations, and psychology TMAS scale. It was analyzed by Wilcoxon signed ranks analysis. From a statistical test Wilcoxon signed ranks test with a significance level of 20% ( α = 12:20 ) was obtained assuming significant 0109 0:20. Ha was accepted, means there was a positive effect between dhikr therapy with decreased anxiety levels of pregnant women in prisons, the higher the level of dhikr, the lower the level of anxiety. It can be concluded that the therapy is effective in reducing the dhikr anxiety levels of pregnant women in prisons.   Keywords: Therapy Dhikr, Anxiety, and Pregnant Women in Prison